Pan-cancer analysis of SETD2 mutation and its association with the efficacy of immunotherapy - Mingdong Lu (Nature Portfolio, 2021)
Abstract Histone methyltransferase SETD2 plays a critical role in maintaining genomic integrity and stability. Here, we investigated the characteristics of SETD2 somatic mutation in the cancer genome atlas pan-cancer cohort. Our data revealed that, compared with SETD2 nonmutant patients, SETD2 mutant patients had higher tumor mutation burden and microsatellite instability. In addition, the transcriptions of most genes related to immune activities were upregulated in patients with SETD2 mutant tumors. Further examination of cancer patients treated with immune checkpoint inhibitors suggested SETD2 mutation was associated with favorable clinical outcomes. These results have implication for the personalization of cancer immunotherapy.